Constructing a measure of adult attachment styles - MEBARKI, Khadidja; BOUFATEH, Mohamed; BAHI, Selami (Social Sciences Journal)
The study aimed at building a measure of attachment patterns in adults and verifying its psychometric properties on a sample of 385 university students from the Faculty of Humanities and Social Sciences of Ammar Thaliji University in Laghouat. The scale was characterized by high cycometric characteristics and proven validity and reliability for the Algerian environment. And included 80 items in its final form represent four patterns are «safe and avoidance and contradictory and separate», and identified the patterns prevailing in the student community where the safe mode ranked first followed by the pattern of contrast and then avoid and then separated.